2010
DOI: 10.1186/1479-5868-7-61
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, psychological, and social influences on physical activity among Japanese adults: structural equation modeling analysis

Abstract: BackgroundAn understanding of the contributing factors to be considered when examining how individuals engage in physical activity is important for promoting population-based physical activity. The environment influences long-term effects on population-based health behaviors. Personal variables, such as self-efficacy and social support, can act as mediators of the predictive relationship between the environment and physical activity. The present study examines the direct and indirect effects of environmental, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
62
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 35 publications
(36 reference statements)
14
62
2
Order By: Relevance
“…Previous studies have shown that the rate of daily steps in employees increased after the intervention, just like the present study [27,37,38]. However, the findings of the current research are inconsistent with those of a study conducted at Catalan University [39].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Previous studies have shown that the rate of daily steps in employees increased after the intervention, just like the present study [27,37,38]. However, the findings of the current research are inconsistent with those of a study conducted at Catalan University [39].…”
Section: Discussioncontrasting
confidence: 97%
“…The results showed that the physical environment had only indirect influence on the physical activity through the social and mental factors but the personal and social factors affected the physical activity, directly and indirectly. This study claimed that the intervention strategies must be used to optimize the physical activity [27]. Bakhtari et al, through investigating the effective factors on the physical activity of women working at Tabriz University showed that the personal factors had direct influence and the social had both direct and indirect (through individual factors) influence on the physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, adults with past pa experience in school have maintained high pa levels (7). With regard to ese that is an important concept of the social Cognitive theory, has been proven that one's belief in his/her ability to persist in exercising had a crucial role in the promotion of pa participation (7,8). In particular, it has been found that ese had the highest positive effect on pa than various other psychosocial and environmental variables (8).…”
Section: Introductionmentioning
confidence: 76%
“…These findings have led to an increased scientific interest in investigating factors that predict adults' participation in pa (5,6). recent studies have indicated that participation in past pa (6,7) and exercise self-efficacy (ese) (7,8) were important positive predictors of pa. specifically, participation in pa at the ages of 10-19 and 40-64 years old has predicted the maintenance of a high level of pa in old age (6). In line with this, adults with past pa experience in school have maintained high pa levels (7).…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire psychometric properties, as well as its validity and reproducibility, are applicable for prevalence studies based on national populations (14,15). Currently, the IPAQ is broadly known as the most objective way of estimating physical activity level (16)(17)(18). The assessment of physical aptitude has been considered relevant for health status because physical activity is a protection factor in relation to the development of chronic non-transmissible diseases, mainly coronary disease and metabolic syndrome (19).…”
Section: Discussionmentioning
confidence: 99%